UJI DAYA TERIMA ROTI TAWAR DENGAN MODIFIKASI TEPUNG JAGUNG DAN KENTANG DAN KONTRIBUSINYA DALAM PEMENUHAN KECUKUPAN ENERGI PADA ANAK SD - Cahya Elika Lubis; Albiner Siagian; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Food diversification instead is necessary to be done in order that food endurance can be guaranteed. It is expected to improve food quality because by more variety consumption, community nutrition will also be more complete than only one variety of food. White bread are usually made using wheat flour is imported foodstuffs, can be modified by making use of local foods such as corn flour. White bread are modified with corn flour and spotato are also potentially contribute nutrients such as protein, fat, calcium, phosphorus, iron, vitamin B1, and vitamin C This was an experimental study on making white bread by adding corn flur and potato in different proportion of wheat flour, corn flour, and potato (5:2:3, 5:2,5:2,5, and 5:1:4). This study was aimed to determine the acceptability which comprised the color, flavor, taste, and texture which were tested by hedonic test and its nutrient composition. The result of this research showed that by organoleptic test of color, flavor, and taste, white bread with the addition of corn flour and potato which made with 5:1:4 proportion was the most favored by the panelists. The addition of corn flour and potato on bread making increased the content of calcium, phosphorus, iron, vitamin B1, and vitamin C than ordinary white bread. Consumption of two pieces of A3 white bread with addition corn flour and potato contributes 14,86% adequacy of energy in 10-12 years old children. It is suggested for consumer to make white bread with addition of corn flour and potato as an alternative health food. In addition, it is necessary to do other foods diversification by added corn flour and potato as a food which rich in nutrient content. Keywords:       White Bread, Corn Flour, Potato, Acceptability Test, Nutrient Composition